Optimization and Validation of a QuEChERS-Based Method Combined with Gas Chromatography–Tandem Mass Spectrometry for Analyzing Pesticide Residues in Edible Insect Samples - Phannika Tongchai; Nootchakarn Sawarng; Anurak Wongta; Udomsap Jaitham; Kunrunya Sutan; Saweang Kawichai; Chuleui Jung; Bajaree Chuttong; Surat Hongsibsong (Molecules)
The increasing popularity of edible insects as a sustainable food source necessitates stringent safety measures to monitor pesticide contamination. This study aimed to assess and enhance a QuEChERS-based extraction method coupled with gas chromatography–tandem mass spectrometry (GC-MS/MS) for the quantification of pesticide residues in edible insects (bamboo caterpillars, house crickets, silkworm pupae, giant water bugs, and grasshoppers) by combining multiple individual insect specimens into a single, homogenized sample—five replicates were tested. The method was optimized by evaluating various extraction parameters and showed strong linearity for all 47 target pesticides, with correlation coefficients (R2) ranging from 0.9940 to 0.9999. The limits of detection (LODs) varied between 1 and 10 µg/kg, while the limits of quantification (LOQs) ranged from 10 to 15 µg/kg. Recovery studies conducted at three fortification levels (10, 100, and 500 µg/kg) revealed recoveries ranging from 64.54% to 122.12%, that over 97.87% of the pesticides exhibited satisfactory recoveries within the range of 70–120%, and relative standard deviations (RSDs) below 20%, between 1.86% and 6.02%. Matrix effects (%MEs) range from −33.01% to 24.04%, and to those that experienced no effect. More than 94% of the analytes showed minimal ion suppression or enhancement. These results conform to the SANTE guidelines for monitoring pesticide residues in edible insects, enhancing food safety standards and safeguarding consumer protection.